answersLogoWhite

0


Best Answer

To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.

User Avatar

Wiki User

โˆ™ 2012-12-13 01:42:29
This answer is:
๐Ÿฆƒ
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is the inverse function of y equals 2x minus 4?
Write your answer...
Submit
Related questions

What is the inverse function of the equation y equals 4x plus 9 Divided by 2x minus 3?

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.


How do you factor 2x to the fourth power minus 162?

2x to the fourth power minus 162 equals -146


What is -2X minus X equals?

-3X


What order pairs to equation x minus 2x equals negative 4 and equation 2x minus y equals 1?

x = 4 and y = 7


What is the inverse of fx equals 2x?

g(x) = x/2


EO equals 2X minus 20 and OC equals 70 minus X solve for X?

40


What is 9 minus 2x equals 35?

If: 9-2x = 35 then x = -13


What is X in X plus 2X minus 5 plus 2X minus 5 plus 2 equals 127?

X=27


What are the order pairs to equation x minus 2x equals negative 4 and equation 2x minus y equals 1?

x = 4 and y = 7 which will satisfy both equations


What is minus 3x equals 2x minus12?

3x=2x-12x=-12


Is this equation a function y equals 3squared plus 2x minus 3 is this a function?

You can tell if an equation is a function if for any x value that you put into the function, you get only one y value. The equation you asked about is the equation of a line. It is a function.


What is 3x plus 4 equals 19 minus 2x?

An equation where x equals 3.


What is 2x plus y equals 1 2x equals minus y equals -5?

It seems to be some kind of simultaneous equation with too many equality signs in it.


What is additive inverse of -2x?

What is additive inverse


If 2x minus 8 equals 4 what does x equal?

6


What is the converse of if x equals 3 then 2x equals 6?

I believe the converse is: if 2x equals 6 then x equals 3 inverse: if x doesn't equal 3 then 2x doesn't equal 6 contrapositive: if 2x doesn't equal 6 then x doesn't equal 3


What is the inverse of the equation y equals 2x plus 3?

x=(y-3)/2


What is the inverse of y equals 2 to the x power?

if y = 2x then x = log2 y


Does the equation y equals 2x plus 1 represent a function?

The [ 2x + 1 ] represents a function of 'y' .


What is the multiplicitive inverse of 3 plus 2x?

The multiplicative inverse of 3+2x is 1/(3+2x).


If 4x minus 7 equals 2x plus 5 what is x?

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.


Y equals 2x-2x-24 determine the roots of the function?

If Y equals 2X - 2X - 24, then there is one root, and it is -24. The two 2X's cancel each other out.


What is 3x squared plus 2x minus 8 equals 0?

3x2 + 2x - 8 = 0 is a quadratic equation.


What is the y-intercept of the equation 2x minus 5y equals -10?

-2


How do you rewrite as a function of x using function notation for 2x plus 3y equals 4?

If 2x + 3y = 4, y= (4 - 2x)/3. In function notation, f(x) = (4 - 2x)/3.